KEDUDUKAN PAJAK DALAM SISTEM EKONOMI ISLAM: STUDI PERBANDINGAN DENGAN SISTEM KONVENSIONAL - Iwandi, Iwandi (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2025)
Taxes are an important instrument in the management of a country's economy, both in Islamic and conventional economic systems. This study aims to analyze the position of taxes in the Islamic economic system and compare it with the conventional system. In Islamic economics, taxes are considered a complement to the zakat mechanism, which is the primary obligation for Muslims. Taxes in Islam serve to meet the state's emergency needs that cannot be covered by zakat, donations, or other sources of income. This differs from the conventional system, which positions taxes as the primary instrument for financing development, distributing wealth, and regulating economic activities. The approach used in this study is descriptive-comparative analysis using primary sources from the Qur'an, Hadith, and classical fiqh books, as well as secondary sources from modern economic literature. The results of the study show that the Islamic economic system prioritizes justice, accountability, and sustainability in tax management. Taxes are only imposed as an emergency measure while still considering Sharia principles, such as the prohibition of usury, uncertainty, and exploitation. Conversely, the conventional system appears flexible in the application of taxes but often leads to inequality due to a system oriented toward state interests without strict ethical boundaries. This study concludes that although there are similarities in the functions of taxes in both systems, the fundamental differences lie in their philosophical foundations, management objectives, and implementation constraints. This study provides insights for the development of a more inclusive modern tax system by integrating Sharia values into the global economy. This study aims to explore the position of taxation in the Islamic economic system by comparing it to the conventional economic system. The focus of the study includes the philosophical foundation, functions of taxation, and its implementation mechanisms. This study uses a qualitative approach with literature analysis and in-depth interviews with Islamic economic experts. The results show that the Islamic economic system emphasizes social justice through a combination of taxes and zakat, while the conventional system focuses on increasing state revenue.